Empirical analysis of different hybridization strategies for solving systems of nonlinear equations - Singh, Bishwesvar Pratap; Mäkelä, Marko M.; Nikulin, Yury (Sciendo, 2025)
This paper considers various hybrid methods for solving a system of nonlinear equations. Extensive numerical experiments confirm the research hypothesis that one particular form of hybridization of the conjugate gradient algorithm with Newton’s method outperforms other hybrid strategies considered in the paper.